Analisis Dimensi Proses Pelarutan Tablet Effervescent Sari Buah Markisa - Ansar Ansar; Budi Rahardjo; Zuheid Noor; Rochmadi Rochmadi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2010)
The aim of this study was to understand dissolution process of the passion fruit effervescent tablet used dimension analysis. The variables of surveyed was mass, volume, moisture content, glass transition temperature, the temperature increases while compression, water volume, water temperature, water density, compression force, and compression velocity. The results showed that factors effect on dissolution process of the passion fruit effervescent tablet was mass, volume, moisture content, glass transition temperature, the temperature increases while compression, water volume, water temperature, water density, compression force, and compression velocity. The soluble solid concentration increased while added dissolution time then occur equilibrium.ABSTRAKTujuan penelitian adalah mengkaji proses pelarutan tablet effervescent sari buah markisa menggunakan analisis dimensi. Variabel yang diamati adalah massa bahan, volume bahan, kadar air, suhu transisi gelas, peningkatan suhu selama pengepresan, volume air, suhu air, densitas air, gaya tekan, dan kecepatan penekanan. Hasil penelitian menunjukkan bahwa faktor-faktor yang berpengaruh pada proses pelarutan tablet adalah massa bahan, volume bahan, kadar air, suhu transisi gelas, peningkatan suhu selama pengepresan, volume air, suhu air, densitas air, gaya tekan, dan kecepatan penekanan. Konsentrasi padatan terlarut meningkat seiring dengan bertambahnya waktu pelarutan kemudian terjadi keseimbangan.